Mapping the Trajectory of Socioeconomic Disparity in Working Memory: Parental and Neighborhood Factors. Issue 4 (29th April 2014) - Hackman, Daniel A.; Betancourt, Laura M.; Gallop, Robert; Romer, Daniel; Brodsky, Nancy L.; Hurt, Hallam; Farah, Martha J.
<x xml:space="preserve">Abstract</x> Working memory (WM) is positively correlated with socioeconomic status (SES). It is not clear, however, if SES predicts the rate of WM development over time or whether SES effects are specific to family rather than neighborhood SES. A community sample of children (n = 316) enrolled between ages 10 and 13 completed four annual assessments of WM. Lower parental education, but not neighborhood disadvantage, was associated with worse WM performance. Neither measure of SES was associated with the rate of developmental change. Consequently, the SES disparity in WM is not a developmental lag that narrows or an accumulating effect that becomes more pronounced. Rather, the relation between family SES and WM originates earlier in childhood and is stable through adolescence.